Corporate Taxation and Dividend Behaviour: A Reply and Extension - Feldstein, Martin S. (Review of Economic Studies, 1972)
Journal Article Corporate Taxation and Dividend Behaviour: a Reply and Extension Get access Martin S. Feldstein Martin S. Feldstein Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 2, April 1972, Pages 235–240, https://doi.org/10.2307/2296876 Published: 01 April 1972